Do informal caregivers experience more burnout? A meta-analytic study. Issue 2 (7th February 2021) - Gérain, Pierre; Zech, Emmanuelle
ABSTRACT: Informal caregivers often report exhaustion when providing care, which can be related to forms of burnout. Yet, there is no systematic inventory of studies comparing caregivers and non-caregivers in terms of burnout. For the present meta-analysis, studies comparing burnout in informal caregivers and non-caregivers were screened and included. Two categories of studies were found: those on family care burnout (spousal or parental burnout) and those on professional burnout (mostly in healthcare). For family care burnout studies, informal caregivers reported more emotional exhaustion, and, to a lesser extent, depersonalization and reduced personal accomplishment than non-caregivers. For studies on professional burnout, workers providing informal care also reported more emotional exhaustion than workers not providing such a care. Overall, the results indicate that providing informal care represents a risk for role burnout. In family care burnout studies, these results confirm the assumption that providing informal care adds extra weight on the individuals' shoulders. In professional burnout, these results support the role accumulation theory, pointing that an additional weight in one's role, i.e., providing informal care, has an impact on another role, work. This work emphasizes the consideration of the multifaceted impact that the caregiving role can have on the individual.